Self-Worth of Social-Political Activists: Theoretical Framework and Systematic Review: Keberhargaan Diri Aktivis Sosial-Politik: Kerangka Teoretis dan Tinjauan Sistematis - Jusfayana, Yuthika; Hudiyana, Joevarian (Universitas Islam Indonesia, 2023)
Activists are dedicated individuals who endeavor to create a substantial and significant influence on pivotal social issues. Their endeavors are propelled by a multitude of diverse factors, including aspects such as social identity, perceptions of fairness, efficacy, and other relevant considerations. These factors lead them to engage in a process of internalization within the collective group they are part of, shaping their sense of self-worth. However, the motivation to achieve self-worth is not always the predominant focus in existing study. Therefore, this study aimed to explained the context of activists’ self-worth through the framework of the Quest for Significance (QFS) theory, employing a systematic literature review method. The systematic literature review follows the Preferred Reporting Items for Systematic and Meta-analysis (PRISMA) protocol, utilizing keywords such as “political activism,” “personal significance,” “fulfilling life activism,” “meaningful activist,” and “activist experience.” The platforms searched include Google Scholar, Springer Nature, Taylor & Francis, and Sage Journal. During the screening stage, journals that met the criteria related to social-political activism and the activation processes of the QFS (significance gain and significance loss) were carefully selected. The study identified key theme concerning the self-worth of activists, such as the role of activism as a coping mechanism, the positive outcomes of activism, the impact of relationships on activist, and challenges inherent in activism.